1974
DOI: 10.1002/aja.1001400305
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic enzyme activity during endochondral ossification of secondary cartilage

Abstract: Reactions for hydrolytic enzymes such as aminopeptidase, p-glucuronidase, N-acetyl-p-glucosaminidase, arylsulfatase and non-specific esterases indicated various degrees of activity within the chondrocytes of the young mandibular condyle. Most of the reaction products of the above enzymes appeared as discrete granules, which might indicate a lysosomal origin. The most intense activity of these enzymes was observed within chondroblasts and premineralizing hypertrophic chondrocytes. However, chondrocytes within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The mature flattened chondrocytes resemble the chon-drocytes described a t the light microscopical level in the flattened cell zone in epiphyseal cartilages of fish (Haines, 1934(Haines, , 1938(Haines, , 1942Meunier, 1979) and of warm-blooded vertebrates (e.g., Howlett, 1979). The chondrocytes in Meckel's cartilage of H. bimaculatus however, seem to lack one feature which is often held to be characteristic for such cells, namely deposits of glycogen (e.g., Godman and Porter, 1960;Silberberg et al, 1964Silberberg et al, , 1966Silberberg et al, , 1976Silva and Hart, 1967;Holtrop, 1972;Silbermann and Frommer, 1974;Silbermann and Lewinson, 1978). The presence of glycogen in chondrocytes is indicative of the state of maturation of the cells and related to the synthesis of matrix polysaccharides (Knese, 1979).…”
Section: Chondrogenesk Of Meckel's Carfikgementioning
confidence: 99%
“…The mature flattened chondrocytes resemble the chon-drocytes described a t the light microscopical level in the flattened cell zone in epiphyseal cartilages of fish (Haines, 1934(Haines, , 1938(Haines, , 1942Meunier, 1979) and of warm-blooded vertebrates (e.g., Howlett, 1979). The chondrocytes in Meckel's cartilage of H. bimaculatus however, seem to lack one feature which is often held to be characteristic for such cells, namely deposits of glycogen (e.g., Godman and Porter, 1960;Silberberg et al, 1964Silberberg et al, , 1966Silberberg et al, , 1976Silva and Hart, 1967;Holtrop, 1972;Silbermann and Frommer, 1974;Silbermann and Lewinson, 1978). The presence of glycogen in chondrocytes is indicative of the state of maturation of the cells and related to the synthesis of matrix polysaccharides (Knese, 1979).…”
Section: Chondrogenesk Of Meckel's Carfikgementioning
confidence: 99%
“…Several cell types have been proposed to be involved in resorption of uncalcified cartilage, such as multinucleated chondroclasts (Muhlhauser, 1983;Aceitero et al, 1988) and enclosed chondrocytes (Schenk et al, 1967;Melcher, 1972;Silbermann and Frommer, 1974;Yoshioka and Yagi, 1988). Except for the possible limited participation of (mononuclear) osteoclasts, we have no evidence of the involvement of such cells during the resorption process of Meckel's cartilage in Hemichromis bimaculatus.…”
Section: Role Of Fibroblast-like Cells In Fhe Resorption Areamentioning
confidence: 99%
“…Studies ofthe function and importance of acid extracellular matrix precedes the mioeralization phosphatase (AcP) have shown that this enzyme of hard tissues has been suggested (14,22). can be found in matrix-producing areas of bone LysosomaJ enzymes have been proposed as and cartilage (13,405,41)-Both enzyme his-mediators of this reduction of glycosaminotochemical (!7,18) and hiochemical studies glycans (19,29,31,33). Electron microscopic (5,38) have produced evidence of two groups of investigations have shown lysosome-like ex-AcP in normal hard tissue forming areas^ one tracellular bodies, matrix vesicles type I (25,37).…”
mentioning
confidence: 99%